Close-spaced plant arrangement optimizes castor biomass and seed yields in tropical fall–winter conditions - Kotz-Gurgacz, Tailene E. [UNESP]; Soratto, Rogério P. [UNESP]; Guidorizzi, Fernando V. C. [UNESP]; Gilabel, Amanda P. [UNESP]; Souza, Emerson F. C. (Wiley, 2022)
The high seed yield and optimum harvesting of short-height castor (Ricinus communis L.) genotypes have enabled its large-scale cultivation and introduction in the Brazilian cropping systems. Thus, studies to optimize plant density are essential to adequate plant population since this is the key management to influence castor biomass and seed production. This study aimed to evaluate the influence of plant density by altering plant arrangement (i.e., spacing between and within rows) on growth, biomass production and partitioning, and seed yield of a castor cultivar in fall–winter cropping season. Field experiments were conducted over two seasons in southeastern Brazil. Two close-spaced (0.45 × 0.23 m and 0.45 × 0.44 m) and a traditional (0.90 × 0.44 m) plant arrangements were tested. Plant arrangements influenced plant growth, biomass production and partitioning, and seed yield. Compared to the traditional layout, close-spaced plant arrangements resulted in thinner basal stems and lower leaf area per plant, but increased leaf area index. The plant arrangement with higher plant density increased per-unit area production of stem plus leaf biomass (43–48%), which also resulted in increased (24%) seed yield, compared to traditional layout. Although a greater amount of biomass was partitioned to reproductive organs in close-spaced plant arrangements, this allocation was not enough to influence the harvest index. Therefore, the adaptive performance of short-height castor adjusting biomass partitioning to maximize stem plus leaf biomass production and seed yield at close-spaced plant arrangement demonstrated this to be a suitable option to cultivate in the Brazilian fall–winter season.